MENGGAGAS PENDIDIKAN AGAMA ISLAM MULTIKULTURAL BERBASIS AL-QURAN Jejak Dan Pengembangan Nilai-nilai Multikulturalisme Dalam Pendidikan Agama Islam - Rohimin Rohimin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
This paper aims  to explore how the concept of multiculturalism in the Medina Charter as an initial  concept applied by the  Prophet to realize multiculturalism in the  practice of pluralist shared life, Affirmation of the  Medina Charter as a preliminary check  in multiculturalism, because the  verses  of the  Koran  at the  time  of the  emergence of the Medina Charter not finished yet. Furthermore, it is explored how then the Koran responds to the Prophet’s politi- cal and  humanist policy steps  in a normative-historical manner in developing multiculturalism as an offer of Islamic concepts for the formation of multiculturalist instruments. The research used is library research (library reseach), which examines the content of the Medina Charter, related verses of the Koran and reading books related to the subject matter. While the  approach used  in this study  is historical-philosophical. The method for analyzing the  data  that  I use is de- scriptive analysis method. The basic assumption is that the policies and strategies developed in the Medina Charter and the response of the verses of the Koran are part of Islamic Education. In developing multiculturalism-based PAI, it is not enough just to normalize the basics, but it needs to be done in a community effort in the Learning Plan. The paradigm of multiculturalism that must be built is how the multicultural theology itself and what are the main principles that can be developed from the reading of the Medina Charter and the verses of the Quran relating to multiculturalism